Characterization of biochars from different sources and evaluation of release of nutrients and contaminants (Revista Ciência Agronômica, 2017)
The biochar, product of pyrolysis of organic waste, has been used as a soil conditioner and alternative onsolid waste management. However, the raw material and pyrolysis temperature used influence the quantity and dynamics ofrelease of nutrients and contaminants from the biochar. The objective was to evaluate the use of waste sugarcane bagasse,eucalyptus and sewage sludge for production of biochar and determine the chemical, physical, mineralogical properties andacid extraction of these materials produced at 350 °C and 500 °C. Were evaluated the proportion of C, H, N, O; ashes; macroand micronutrients, plus some contaminants; characterization of mineral phases by diffractometry of X- rays; functionalgroups by infrared absorption spectroscopy (FTIR). Moreover, it was determined the release of nutrients and contaminantsfor the extraction in increasing concentration of HNO3(0,01 - 2,0 mol L-1). The O/C and H/C relations decreased withincreasing temperature of pyrolysis, which define a greater stability of the C of biochars. Sewage sludge biochar (BC-L) hadthe highest nutrient release rates and contaminant metals (Cd, Cr, Ni and Pb). Acid extraction of other biochars was very low(